A signal-on fluorescent sensor for ultra-trace detection of Hg2+ via Ag+ mediated sulfhydryl functionalized carbon dots. (August 2019) - Han, Yong; Shi, Limei; Luo, Xueli; Chen, Xiumei; Yang, Weixia; Tang, Wenzhi; Wang, Jianlong; Yue, Tianli; Li, Zhonghong
Abstract: Sulfhydryl functionalized carbon dots (HS-CDs) mediated by Ag + were used to develop a fluorescent sensor for the determination of Hg 2+ in aqueous solutions. FTIR and XPS confirmed the successful modification of -SH on the surface of HS-CDs. Dripping Ag + into HS-CDs yielded brown agglomerates of silver thiolate leading to strong FL quenching of the HS-CDs. The signal-on fluorescent sensor was acheived by dispersing the precipitates in a PBS buffer (pH 7.4, 0.01 mol/L). Remarkable FL recovery was observed upon the addition of Hg 2+ into the sensor owing to the energy trap induced by exposure of -NH2 on the surface of the HS-CDs. Fluorescence intensities of the HS-CDs were linearly recovered in Hg 2+ concentrations of 0.01–0.75 nmol/L with an extremely low detection limit of 4.2 pmol/L. The sensor exhibited stronger specificity toward Hg 2+ than co-existent metal ions. The detecting results for real water samples obtained by the sensor showed good agreement with ICP-AES (P > 0.05), demonstrating a sensitive and selective fluorescent nanosensor for ultra-trace determination of Hg 2+ with acceptable precision and satisfactory accuracy. Graphical abstract: Image 1